Reducing Attrition in Physical Activity Programs for Older Adults - Jancey, Jonine; Lee, Andy; Howat, Peter; Clarke, Ann; Wang, Kui; Shilton, T. (Human Kinetics Inc, 2007)
This study investigated attrition in a 6-month physical activity intervention for older adults. The program was based on the social-cognitive theory incorporating self-efficacy factors. Two hundred forty-eight insufficiently active 65- to 74-year olds were recruited from the Australian federal electoral roll. The intervention comprised walking and strength and flexibility exercises and was conducted in 30 local neighborhoods where the participants resided. Characteristics of individuals lost to attrition (n = 86, 35%) were compared with those of programcompleters (n = 162, 65%). Logistic-regression analysis showed that those lost to attrition came from areas of lower socioeconomic status, were overweight and less physically active, and had lower walking self-efficacy scores and higher loneliness scores. The results suggest that early assessment of these characteristics should be undertaken to identify individuals at risk of attrition, to improve retention, and to avoid potential bias.